The Effect of Workload and Organizational Culture on Employee Performance at the Bawaslu of North Toraja Regency - Jannar Tampang; Adriana Madya Marampa; Dina Ramba (Brilliant International Journal Of Management And Tourism, 2025)
The purpose of this study was to examine the effect of workload and organizational culture on the performance of Bawaslu employees in North Toraja Regency. This research employs a quantitative approach to analyze the relationships among the variables. Workload is defined as the amount of tasks, responsibilities, and time pressure experienced by employees, while organizational culture encompasses shared values, norms, and practices that shape employee behavior within the organization. Employee performance refers to the ability of employees to achieve organizational goals effectively and efficiently. The results of this study indicate that workload has a positive and significant effect on employee performance, with a Tcount value of 3.146, which is greater than the Ttable value of 2.131, and a significance level of 0.002, which is less than 0.05. This suggests that an optimal workload can enhance employee performance by motivating employees and improving task management. Similarly, organizational culture positively and significantly influences employee performance, with a Tcount value of 2.692 > Ttable 2.131 and a significance level of 0.008 < 0.05. A supportive organizational culture fosters collaboration, communication, and commitment, which in turn improves individual and team performance. Furthermore, workload and organizational culture together have a significant combined effect on employee performance, as evidenced by an Fcount value of 12.487 > Ftable 3.68 and a significance level of 0.001 < 0.05. These findings highlight the importance of managing employee workload appropriately while cultivating a positive and supportive organizational culture to optimize employee performance. The study provides practical insights for policymakers and managers in Bawaslu and similar institutions to enhance productivity and achieve organizational objectives effectively.